The construction of intelligent nursing and healthcare management platform (智能化健康护理管理平台建设探索) - ZHANG Yuhong (张育红); ZHANG Yuxia (张玉侠) (中西医结合护理)
The intelligent nursing and healthcare management platform focuses on the data-driving healthcare management model, advocates the core concept of "prevention is better than treatment", proposes the service concept of "pre hospital prevention, in hospital treatment and post hospital intervention", collects the whole process and all-round health-related data such as patient physiological monitoring signs, laboratory tests, disease treatment, diet and activities. By using cloud computing and artificial intelligence technology, the intelligent health care management platform aims to establish health care decision-making models, such as evaluation, prediction and intervention, and provide personalized health management services. (智能化健康护理管理平台聚焦数据驱动的健康护理管理模式, 提倡“预防优于治疗”的核心观念, 围绕“院前预防、院中治疗和院后干预”服务理念, 收集患者生理监测、化验检查、疾病治疗、饮食、活动等全程、全方位的健康相关数据, 借助云计算、人工智能技术, 建立评估、预测、干预等健康护理决策模型, 提供个性化的健康管理服务。)